Penerapan Good Governance Dalam Pelayanan Administrasi Terpadu Kecamatan (PATEN) Di Kota Padangsidimpuan - Pasaribu, Safran Efendi; Parapat, Natalia; Telaumbanua, Anita (Universitas Muhammadiyah Tapanuli Selatan, 2024)
The District Integrated Administrative Service Program (PATEN) is one form of innovation in improving services to the community. So that it can create good governance. The main elements that must be met for the formation of good governance are through indicators of rule of law, accountability, transparency, professionalism, and participation. This paper aims to analyze the implementation of integrated sub-district administrative services in the aspect of good governance at the Padangsidimpuan Utara District Office, Padangsidimpuan City. The research method used is qualitative research with a descriptive analysis approach. Data collection techniques through observation, interviews, and literature study. The data analysis technique is carried out by reducing the data, presenting the data and then drawing conclusions in the form of data findings to answer the research objectives. The results of the study concluded that the sub-district integrated administrative service program has not been able to improve the public service system to the community in the process of providing fast service because it has not paid attention to aspects of good governance